‘We hid our stock in case we were raided’: Scotland’s pioneering LGBTQ+ bookshop - Goh, Katie (The Guardian, 2023)
Opened two years after the country legalised ‘homosexual acts’, Lavender Menace made a huge impact. Now it has opened a public queer books archive.
United Kingdom
Keywords: 2023-07 July; Books; Booksellers; Culture; Edinburgh; LGBTQ+ rights